1990
DOI: 10.1037/0735-7036.104.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Experimental determination of a unit of song production in the zebra finch (Taeniopygia guttata).

Abstract: Zebra finch (Taeniopygia guttata) song is composed of syllables delivered in a set order. Little is known about the program that controls this temporal delivery. A decision to sing or not to sing may or may not affect the entire song. Song, once commenced, may continue or may halt. If song is halted, stops may occur only at certain points. Seven zebra finches were presented with short bursts of strobe light while engaged in song. The variables of interest were whether the birds stopped and where they stopped. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
96
3

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(105 citation statements)
references
References 26 publications
6
96
3
Order By: Relevance
“…In contrast, on AAF trials, song interruptions frequently occurred immediately after the targeted syllable, or the completion of the subsequent syllable. Similar interruptions of ongoing zebra finch song have been reported previously in response to disruptions of auditory feedback and stroboscopic flashes (Cynx, 1990;Cynx and von Rad, 2001). In our experiments, interruptions were most prevalent during initial exposure to AAF and then rapidly habituated (see below, Persistence of effects), suggesting that they might reflect a startle response to unexpected stimuli.…”
Section: Song Interruptionssupporting
confidence: 51%
See 2 more Smart Citations
“…In contrast, on AAF trials, song interruptions frequently occurred immediately after the targeted syllable, or the completion of the subsequent syllable. Similar interruptions of ongoing zebra finch song have been reported previously in response to disruptions of auditory feedback and stroboscopic flashes (Cynx, 1990;Cynx and von Rad, 2001). In our experiments, interruptions were most prevalent during initial exposure to AAF and then rapidly habituated (see below, Persistence of effects), suggesting that they might reflect a startle response to unexpected stimuli.…”
Section: Song Interruptionssupporting
confidence: 51%
“…However, although the real-time influence of auditory feedback on speech is well documented, evidence for a similar contribution of auditory feedback to ongoing songbird vocalizations is much more limited (Lee, 1950;Elman, 1981;Howell and Archer, 1984;Houde and Jordan, 1998;Larson et al, 2000;Cynx and von Rad, 2001). Previous studies in zebra finches have shown that song can be interrupted abruptly by unexpected stimuli (Cynx, 1990;Cynx and von Rad, 2001). We similarly found that such interruptions could be elicited by initial exposure to feedback perturbation, but these interruptions, suggestive of a startle response, rapidly habituated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several lines of evidence suggest that this acoustic hierarchy is embedded within the underlying representation for song. Flashes of light cause birds to interrupt their song at syllable boundaries (Cynx, 1990;Franz and Goller, 2002), and the patterns of inspiration/expiration segment the song into syllables and acoustic gaps (Wild et al, 1998;Suthers and Margoliash, 2002;Goller and Cooper, 2004). Early electrophysiological experiments suggest that this structure is reflected in the anatomical hierarchy in the forebrain, with nucleus HVC (used as a proper name) being responsible for syllable sequence and nucleus robust nucleus of the arcopallium (RA) representing individual syllables (Vu et al, 1994;Yu and Margoliash, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…When interrupted by a strobe flash in the midst of a syllable, a zebra finch will complete the syllable, which suggests that these chunks are units of motor planning (Cynx, 1990). A sequence of several syllables that repeats during the course of a song is called a motif (Slater, 2000).…”
Section: Hierarchical Structurementioning
confidence: 99%